Are there sex differences in the association between the 5HTT gene and neuroticism? A meta-analysis - Munafo, MR; Clark, T; Flint, J (2004)
An association between polymorphism in the serotonin transporter gene linked promoter region (5HTT-LPR) and the human personality trait of neuroticism has been reported. One potentially important factor moderating the genetic effect of this polymorphism on neuroticism is sex. We sought to address the question of whether sex moderates the association between the 5HTT-LPR polymorphism and anxiety-related personality traits in humans by means of meta-analytic techniques. Transformed personality trait scores were entered into a 2 × 3 ANOVA with sex (male, female) and genotype (ss, sl, ll) as between-subject factors. This indicated a main effect of sex (p=0.04) and genotype (p=0.01) on personality. The interaction was not significant (p=0.65). The results of this meta-analysis do not offer any support for a moderating effect of sex on the association of the short allele of the 5HTT gene with neuroticism. © 2003 Elsevier Ltd. All rights reserved.